Analisis Framing Walkout Amerika Serikat di G20 Pada Kompas.Com - Novanda Zahwa Firdhaus; Nurtyasih Wibawanti Ratna Amina (DIGICOM : Jurnal Komunikasi dan Media, 2023)
This research is entitled "Analysis of the US Walkout News Framing in the G20 Meeting on Kompas.com Online Media". To complete this research, the researcher used six news scripts, which were motivated by the US exit from the G20 forum to boycott Russia who attended the forum after its invasion of Ukraine. The object of this research is the online media Kompas.com which makes the news. In this study, the researcher wanted to know how Kompas.com framed the news. The analytical method used is the method of Robert N Entman which has four elements, namely Define Problems (defining the problem), Diagnose Causes (estimating the problem or source of the problem), Make Moral Judgment (making moral decisions), Treatment Recommendation (emphasizing completion). The results of the study show that Kompas.com uses the issue selection process used in every news story that discusses the US walkout at the G20 forum. So that it shows that the news presented by Kompas.com tries to convey the highlight of the issue by showing the truth of the facts from the sources who were there at the time of the incident and understood the issues that occurred.